Innocent of Moscow, the apostle of Kamchatka and Alaska - Hale, Charles R. (Charles Reuben), 1837-1900.; Innokentiĭ, Saint, Metropolitan of Moscow and Kolomna, 1797-1879. Correspondence. English. Selections. 1877. ([U.S. : s.n.], 1877)
Includes selections from Innocent's letter. "Reprinted from the July 1877 number of the American church review." "Privately printed." Mode of access: Internet.